2012
DOI: 10.2174/138161212801327220
|View full text |Cite
|
Sign up to set email alerts
|

The Redox Biology of Schistosome Parasites and Applications for Drug Development

Abstract: Schistosomiasis caused by Schistosoma spp. is a serious public health concern, especially in subSaharan Africa. Praziquantel is the only drug currently administrated to treat this disease. However, praziquantel-resistant parasites have been identified in endemic areas and can be generated in the laboratory. Therefore, it is essential to find new therapeutics. Antioxidants are appealing drug targets. In order to survive in their hosts, schistosomes are challenged by reactive oxygen species from intrinsic and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 221 publications
(345 reference statements)
0
57
0
Order By: Relevance
“…We thus thought that PCS could be regulated as part of a comprehensive antioxidant GSH-dependent defense mechanism [22]. Metals have been shown to affect the transcript levels of γ-GCS in Saccharomyces cerevisiae [48] and in plants [49] and of PCS [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus thought that PCS could be regulated as part of a comprehensive antioxidant GSH-dependent defense mechanism [22]. Metals have been shown to affect the transcript levels of γ-GCS in Saccharomyces cerevisiae [48] and in plants [49] and of PCS [50].…”
Section: Discussionmentioning
confidence: 99%
“…Schistosomiasis affects more than 200 million people in more than 70 tropical and sub-tropical countries and causes more than 200,000 deaths annually [20]. Chemotherapy is the major control measure for schistosomiasis and currently only a single drug, praziquantel, is available [21], [22]. Monotherapy for such a widespread and prevalent disease raises serious concerns about the selection of drug resistant parasites [21].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which NAPQs exerts their in vitro schistosomicidal effect is not clear at the present time. However, it is generally recognized that mechanisms of antiparasitic activity involve modulation of parasite redox cycling (reduction and oxidation cycle of quinones in flavin enzymes such as NADPH-cytochrome P450 and mitochondrial NADH-ubiquinone oxidoreductase) and production of reactive oxygen species (ROS) leading to severe oxidative stress by oxidizing essential macromolecules, such as proteins, lipids and DNA [47,48]. Studies have shown that NAPQs are potent electrophiles and they are also capable of directly reacting with thiol groups of S. mansoni parasite proteins and glutathione resulting in inhibition of enzymes essential for parasite survival [43,49].…”
Section: Discussionmentioning
confidence: 99%
“…The first is by Dr. David Williams, who along with his colleagues has been developing new approaches to treat helminth infections. For example, reasoning that schistosomes are highly dependent on the production of anti-oxidants to protect themselves from host immune attack, and that schistosomes have a redox network distinctly different from our own, he has pointed out that compounds that target distinctive schistosome redox enzymes may become clinically relevant in the near future (Huang et al, 2012). Also, Dr. LoVerde, at this year’s ASP meeting, pointed out significant advances in identifying a sulfotransferase locus (SmSULT) involved in conferring resistance to the anti-schistosome drug oxamniquine.…”
Section: Helminth Elimination Efforts Provides Many Opportunities Anmentioning
confidence: 99%